Partnership in Practice: Implementing Healey’s Conceptual Model - Ahmad, Arshad; Ali, Aadil; VanMaaren, John; Barrington, Janette; Merritt, Olivia; Ansilio, Kyle (International Journal for Students as Partners, 2017)
This case study discusses the implementation of Healey, Flint, and Harrington's (2014) model of student engagement through partnership with staff. Healey et al. (2014) identify issues associated with “putting partnership into practice” including inclusivity and scale, power relations, reward and recognition, transition and sustainability, and identity. Faculty, staff, and students participating in a Students as Partners (SaP) Program at McMaster University’s MacPherson Institute encountered these issues during a Scholarship of Teaching and Learning (SOTL) project. This paper explores our reflections and suggests refinements related to the above five issues. It concludes by identifying possible new directions for SaP programs.